2012
DOI: 10.1242/dev.081190
|View full text |Cite
|
Sign up to set email alerts
|

Kif7 regulates Gli2 through Sufu-dependent and -independent functions during skin development and tumorigenesis

Abstract: SUMMARYAbnormal activation of Hedgehog (Hh) signaling leads to basal cell carcinoma (BCC) of the skin, the most common human cancer. Gli2, the major transcriptional activator of Hh signaling, is essential for hair follicle development and its overexpression in epidermis induces BCC formation and maintains tumor growth. Despite its importance in skin development and tumorigenesis, little is known about the molecular regulation of Gli2. Sufu and Kif7 are two evolutionarily conserved regulators of Gli transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 45 publications
3
61
0
Order By: Relevance
“…Consistent with previous reports, the expression of Ptch1, the SHH receptor, was not detected. Kif7 is a key regulator of Hh signaling in neural tube (19), limb (20), bone (27), and skin development (28), and Hh signaling promotes cell proliferation in several systems by regulating the expression of the cell cycle regulating gene, Cyclin D1 (Ccnd1) (11). Hence, we examined the expression and counted the number of Ccnd1 + cells in the E12.5 diaphragms of Kif7 dd/dd mutant embryos, and we determined that the number of Ccnd1 + cells was increased approximately twofold compared with cells in littermate controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with previous reports, the expression of Ptch1, the SHH receptor, was not detected. Kif7 is a key regulator of Hh signaling in neural tube (19), limb (20), bone (27), and skin development (28), and Hh signaling promotes cell proliferation in several systems by regulating the expression of the cell cycle regulating gene, Cyclin D1 (Ccnd1) (11). Hence, we examined the expression and counted the number of Ccnd1 + cells in the E12.5 diaphragms of Kif7 dd/dd mutant embryos, and we determined that the number of Ccnd1 + cells was increased approximately twofold compared with cells in littermate controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Structure-function analyses have shown that C-terminal sequences are required for positive inducing activity and cytoplasmic localization, whereas N-terminal sequences determine dominant negative function and nuclear localization [22]. There are two important regulators of the GLI proteins, Sufu that forms complex with GLI proteins and prevents its nuclear accumulation, and Kif7 that promotes activation through dissociation of Sufu-GLI2 complexes to allow translocation of GLI2 into the nucleus [23]. The strong predictive and prognostic value of GLI2 in our series, in contrast to GLI1 and GLI3, supports this assumption.…”
Section: Discussionmentioning
confidence: 99%
“…The full-length GLI2 is bound to SuFu, and thus SuFu keeps GLI2 tethered in the cytoplasm [7,9,10] . Another member of the pathway, Kif7, can antagonize SuFu by disrupting the SuFu/GLI2 complex and allowing nuclear translocation of GLI2 [80] . The absence of Hh signaling results in the predominance of GLI2 protein maintained in a repressive state while active Hh signaling reverses this repression.…”
Section: Canonical Modulation Of Gli2 Protein Activitymentioning
confidence: 99%